Correlations of fetal-maternal outcomes and first trimester 3-D placental volume/3-D power Doppler calculations - (:unkn) unknown (I R O G CANADA, INC, 2010)
Objective: To investigate correlations between first trimester placental volume, placental vascularization indexes and the outcome of those pregnancies. The possible prediction of macrosomia and intrauterine growth restriction in the first trimester are studied. Methods: We prospectively examined 145 pregnant patients at 11-14 weeks of gestation using transvaginal 3D gray-scale and power Doppler ultrasound. The acquired volumes were analyzed using the VOCAL imaging program, for assessing placental volume, vascularization index (VI), flow index (FI) and vascularization flow index (VFI). The results were correlated with the pregnancy Outcome. Results: Correlations between placental volume and the intrauterine growth restriction group of infants classified according to their anthropometric measurements were significant. As the placental volume decreases, percentage of intrauterine growth restriction increases. In the aspect of placental vascularisation indexes, VI showed a positive lineer correlation with newborn weight. Conclusion: The 3D placental volume and blood flow calculations could be important in the prediction and easy, rapid diagnostic evaluation of fetal growth restriction presenting with placental Volume and vascular tree alterations even beginning at the first trimester.
Keywords: 3-D ultrasound; VOCAL; Placental volume; IUGR; Pregnancy outcome; 2ND TRIMESTER; 2ND-TRIMESTER; VASCULARIZATION; PREGNANCIES; ULTRASOUND; BIRTH